Evaluation of an existing activity on pragmatics - qizi, Murodova Iroda Alisher (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
Since pragmatic ability is defined by the comprehension through both productive and receptive skills which are reading , listening, speaking and writing both native and non-native speakers are expected not only to be able to understand direct or literal meaning of written or oral messages, but also implied or hidden sense of the delivered message to be acknowledged as pragmatically competent. Whether the user of the language is pragmatically successful in reception and production the language stems from various contributory factors such as “proficiencyin L2, age, gender, occupation, social status, and experience in the relevant L2-speaking communities, and previous experiences with pragmatically competent L2 speakers and multilingualexperiences in general”. (Ishihara,2010).